Financial Development, Financial Openness and Trade Openness: New evidence - Pham Thi Hong Hanh (FIW - Research Centre International Economics, 2010)
Employing the Pedroni co-integration technique and the GMM estimator, this paper aims at investigating the possible connection between financial development, financial openness and trade openness in twenty-nine Asian developing countries over 1994-2008. Firstly, we find a bidirectional causality between trade openness and financial development/openness. Secondly, the relationship between financial development and financial openness is heterogeneous across different measures. Finally, this paper provides a complementary contribution to earlier studies as asking for the question of whether the inclusion of financial crisis in estimated models can change the nature of the relationship between financial development and both types of openness.
Keywords: D90; F14; F36; G01; O16; 330; Financial development; Financial Openness; International Trade; Financial Crisis; Developing countries; Panel Co-integration